(untitled) (Repertorio Científico, 2025)
Objective. Analyze water quality by means of aquatic macroinvertebrates for the prioritization of water resource conservation measures. Methods: the quantitative approach was used, the methodology used for the analysis of water quality was based on the Regulation for the evaluation and classification of the quality of surface water bodies, Decree N 33903-Minae-S, the macroinvertebrates were valued with the BMWP-CR (Biological Monitoring Working Party) index modified for Costa Rica. Results: the base year presents poor quality water, highly contaminated related to the contaminant load of anthropogenic activities that take place in the sector that improves with the intervention of environmental management measures implemented in the body of water. Conclusion: The evaluated transect of Quebrada La Cabra registered a significant improvement in water quality, going from poor to regular quality with moderate contamination, influenced by the management actions implemented with the micro-basin ecological blue flag program.